Lima Barreto: O Brasil sob a ótica do Dr. Bogóloff - Costa, Fabiano da Silva [UNESP] (2015)
Lima Barreto lived in a period when Brazilian Literature was searching for different artistic manifestations. In that scenario, Lima Barreto's writings present a new literary proposal in which identity plays a central role in his aesthetics. The reader should notice that this identity is connected to the grotesque and the absurdity of the culture of favor, and this notion brings about the author's satirical vision. Dr. Bogóloff, a character who appears in the unfinished novel Aventuras do Doutor Bogóloff (1956) and also in the novel Numa e a Ninfa (1915), points out our customs and behavior through his foreigner's eyes.. In order to analyze the identity issues addressed by Dr. Bogóloff, the concepts of identity, attribution of identity and national identity by Hall (2000), Woodward (2000), Silva (2000) and Bourdieu (2011) will be used. Lima Barreto's aesthetics are as important as his social criticism in constructing the identity of his characters, among them Dr. Bogóloff